Compassion Satisfaction, Compassion Fatigue and Hardiness Among Nurses: A Comparison Before and During the COVID-19 Outbreak - Zakeri, Mohammad Ali; Rahiminezhad, Elham; Salehi, Farzaneh; Ganjeh, Hamid; Dehghan, Mahlagha (Frontiers in Psychology, 2022)
Background Nurses provide the majority of health-care services and face numerous health challenges during an epidemic. During the COVID-19 epidemic, nurses are subjected to physical, mental, and social disorders that impair their quality of life and hardiness. Therefore, it is important to be aware of the situation of nurses. The current study aimed to compare the compassion satisfaction, compassion fatigue and hardiness among nurses before and during the COVID-19 outbreak. Materials and Methods This cross-sectional study included 508 clinical nurses from one public hospital in southern Iran. The subjects were recruited using census sampling methods in 2019–2020. Sampling was performed before (n = 266) and during the COVID-19 (n = 242) with a 1-year interval. Although, the study setting was the same before and during the COVID-19, questionnaires were completed by different nurses before and during the COVID-19. Demographic questionnaire, professional quality of life (ProQOL) questionnaire and Occupational Hardiness Questionnaire were used to collect data. Results The scores of compassion satisfaction, compassion fatigue and hardiness did not differ significantly during the COVID-19 compared with before the COVID-19 (p > 0.05). Before COVID-19, hardiness and work experience predicted 11% of the variance of compassion satisfaction, whereas during COVID-19, hardiness and gender predicted 26% of the variance of compassion satisfaction. Before COVID-19, hardiness and work experience predicted 3% of the variance of compassion fatigue, whereas during COVID-19, hardiness, type of employment and gender predicted 6% of the variance of compassion fatigue. Conclusion The current study found that compassion satisfaction, compassion fatigue and hardiness did not change during the COVID-19 outbreak compared with before the COVID-19 outbreak. However, during the COVID-19, the hardiness was a significant predictor of compassion satisfaction and compassion fatigue. The study results showed that it was possible to increase the compassion satisfaction and reduce the compassion fatigue by strengthening the hardiness of nurses. However, these results need to be considered in future studies, especially in crises such as COVID-19 disease.